Comparative Effects of Fermentation of Sugar Kefir Grains (Tibicos) And Tetracyclin On Three Major Ileum Bacteries In Broiler Chickens - Hilmi, Mustofa (Program Studi Peternakan, Fakultas Pertanian, Sains dan Kesehatan, Universitas Timor, 2025)
Antibiotics such as tetracycline in the livestock industry face severe restrictions due to increasing antimicrobial resistance. Tibicos fermentation, as a natural probiotic, has the possibility to be an adequate and safe alternative for modulating gut microbiota. The study aimed to compare the effectiveness of tibicos fermentation and tetracycline in modulating the population of three major bacteria (Escherichia coli, Lactobacillus, and Salmonella spp.) in the ileum of broiler chickens. Ninety Indian River strain broilers were divided into three treatments with three replicates (n=10 per replicate): control with pure water (KN), 45 ppm tetracycline (KP), and 5% tibicos fermentation (FT). Treatments were given through drinking water ad libitum from 8 to 35 days of age. Bacterial populations were analyzed using the Total Plate Count (TPC) method on ileal samples aged 35 days. Data analysis used a multivariate approach including Bray-Curtis dissimilarity, PERMANOVA, Principal Coordinates Analysis (PCoA), and Similarity of Percentage Analysis (SIMPER). Bray-Curtis dissimilarity analysis showed moderate differences in microbiota composition between treatments with values of 0,064854 (FT vs KN), 0,069687 (FT vs KP), and 0,07451 (KN vs KP). SIMPER analysis identified E. coli as the primary contributor to differences between treatments, with contributions of 39,50% (KP vs KN, p=0,005), 65,70% (KP vs FT, p=0,001), and 41,10% (KN vs FT, p=0,001). Principal Coordinates Analysis showed apparent clustering between treatments, with tibicos fermentation producing microbiota profiles that differed from control and tetracycline. Tibicos fermentation showed comparable effectiveness to tetracycline in modulating ileal bacterial composition, particularly in controlling pathogenic populations while maintaining Lactobacillus stability.